Tube bending - Cook, Jerome T.; Green, Richard G.; Society of Manufacturing Engineers ([Dearborn, Mich.] : Society of Manufacturing Engineers, 2003)
An educational program which introduces the various materials and methods used for bending and end forming tubes
Code no : DV03PUB31
Title from title screen
Executive producer, Stephen R. Bollinger ; video editing, Jim O'Donnell
Keywords: Tube bending; Tubes, Steel; Tube industry